Case Report: Metastatic renal cell carcinoma to the thyroid— A rare encounter - Shepherd, Megan; Lohmann, Justin; Nodit, Laurentia; Vaghaiwalla, Tanaz; Mancini, Matthew (Frontiers in Surgery, 2022)
Background: Renal cell carcinoma (RCC) accounts for approximately 4% of new adult cancers.1 By fine needle aspiration, identification of metastatic RCC to thyroid is challenging, therefore surgical resection is indicated for definitive characterization. Our report surveys metastatic RCC to thyroid in our hospital. Methods: Twenty years retrospective review of electronic records in our institution identified five patients with metastatic renal cell carcinoma to the thyroid. We analyzed patient charts and pathology reports to evaluate clinical parameters and therapy. Results: In all cases, original RCC was of clear cell type. Pathologic tumor stage ranged from pT1a to pT3a, Fuhrman nuclear grade varied from 2-4 and angio-lymphatic invasion was noted in one case. In three patients, RCC in the thyroid occurred as an olygometastasis with no evidence of disease in the nephrectomy bed or other parts of the body. In two patients, concomitant recurrent RCC and metastases. The thyroid metastases were found approximately 10 years after completion nephrectomy with a range of 0-21 years. Three thyroid fine needle aspirations correctly identified the disease, one was negative, and one was classified as atypical cells present, suspicious for RCC. Conclusion: Thyroid gland is an uncommon location for RCC metastasis and can appear across a wide range of initial stages and grades of the disease. Thyroid metastases occurred as late as 21 years from the initial tumor resection. Increased awareness and a high index of suspicion is needed to detect metastasis, as they can be found in atypical locations and mimic primary disease.